Efficacy of manual removal and parenteral antibiotic therapy for retained foetal membranes in cattle - KULASEKAR, K; SARAVANAN, D; SENTHIL KUMAR, G; SRINIVASAN, R; SENRAYAN, M (The Indian Journal of Animal Reproduction, 2023)
Retained foetal membrane is an economically important post partum complication in dairy cattle. This study wasundertaken to compare the efficacy between manual removal versus non-removal of retained foetal membranes, with parentralantibiotic therapy . Forty crossbred cows which retained the foetal membranes beyond 8 - 12 hours after normal calving, wererandomly distributed into two groups. Group I cows were subjected to manual removal and parentral antibiotic therapy and GroupII cows were subjected only to parentral antibiotic therapy. In both the groups the nature of lochia, uterine involution and milk yieldwere assessed once in 48 hours until recovery. There was no significant difference in the duration of uterine involution and milk yieldbetween the groups. Parentral antibiotic therapy without manual removal can be suggested as a choice of therapy for retention offoetal membranes.
Keywords: Retained foetal membrane; lochia; uterine involution